Competition of trade and investment between Guangzhou and BRI countries : an empirical analysis based on Export Similarity Index - Luo, Xiaofei (2018)
Trade and investment are significant aspects in economic cooperation between Guangzhou and BRI (Belt and Road Initiative) countries. To solve its economic dilemma in export and manufacturing sector, Guangzhou should try to identify the BRI regions to promote overseas production capacity cooperation, especially in trade and investment. By dividing the BRI countries into six regional groups and using a modified ESI (Export Similarity Index) model, this paper aims to examine the level of competition between Guangzhou and various BRI regional groups from perspectives of trade and investment. From the results, we find that Guangzhou has the highest competition level with ASEAN and South Asian countries in trade while in investment, ASEAN and Central and Eastern Europe are the most potent competitors for Guangzhou. We think there are insightful implications within the empirical analysis and could promote the efficiency of Guangzhou's trade and outward investment under the BRI framework.